2001
DOI: 10.1001/jama.285.15.1978
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness of St John's Wort in Major Depression

Abstract: In this study, St John's wort was not effective for treatment of major depression.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

2
157
1
6

Year Published

2001
2001
2016
2016

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 351 publications
(176 citation statements)
references
References 31 publications
2
157
1
6
Order By: Relevance
“…22,23 Two recent studies found it to be ineffective for patients with severe depression. 24,25 Enthusiasm for the use of St. John's wort is tempered by the many well-documented drug interactions.…”
mentioning
confidence: 99%
“…22,23 Two recent studies found it to be ineffective for patients with severe depression. 24,25 Enthusiasm for the use of St. John's wort is tempered by the many well-documented drug interactions.…”
mentioning
confidence: 99%
“…Movina † is used in Sweden for indications of mild depression, mild anxiety disorders, and occasional sleep disturbances. The documentation in depression is contradictory and studies where the effects seem to be poor have been published [9]. On the other hand, there are also studies suggesting a good antidepressive effect, well in line with conventional therapy [10].…”
mentioning
confidence: 99%
“…1 Despite the controversy on the effectiveness of SJW as an antidepressant, the use of SJW has been widespread and several preparations containing SJW are commercially available in Europe and in the US. Even though two recent multicenter trials in the USA have failed, 2,3 randomized clinical studies have shown that SJW extracts are significantly superior to placebo and similarly effective as standard antidepressants in the treatment of mild to moderately severe depression. [4][5][6] Significant drug interactions have been reported with cyclosporine and protease inhibitors, 7,8 but a commonly cited advantage of SJW continues to be its favorable side effect profile.…”
mentioning
confidence: 99%